The Effectiveness of the Project-Based Learning Model Integrated with Digital Teaching Materials and Computational Thinking to Improve the Habits of Mind of Elementary School Students - Mardhatillah; Ade Eka Anggraini; Sri Rahayuningsih; Mohammad Yusuf Randy (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to test the effectiveness of the Project-Based Learning (PjBL) learning model that is integrated with digital teaching materials and computational thinking in improving the Habits of Mind of elementary school students in Malang Regency. The research approach used is quantitative with a pre-experiment type experimental design, using a one-group pretest-posttest design. The research instrument is in the form of pretest and posttest questions designed to measure the development of students' Habits of Mind before and after the application of the learning model. The results of data analysis showed a significant increase in posttest scores compared to pretests, with an average difference of 13.28 points and a significance value (Sig. 2-tailed) of 0.000. These findings indicate that the Project-Based Learning model that is integrated with digital teaching materials and computational thinking is effective in improving students' Habits of Mind. Thus, this model is recommended as an alternative learning strategy that is innovative and relevant to be applied at the elementary school level, especially in forming a critical, reflective, and adaptive mindset in students.